Evaluating the Potential of Modified Niobium (V) Oxide as Catalyst for 5-Hydoxymethylfurfural (HMF) Production : A Literature Review - Inten Pangestika; Imas Masriah; Devi Lestari; Ayu Syufiatun Br Tarigan; Pina Budiarti Pratiwi (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
Selectively producing 5-hydroxymethylfurfural (HMF) from biomass-derived carbohydrates is key in valorizing renewable resources into biobased chemicals and fuels. HMF is a crucial bio-based platform chemical, but its selective production from glucose and fructose remains challenging due to side reactions and product degradation. Modified niobium(V) oxide (Nb2O5) catalysts have shown great promise owing to their intrinsic Brøntsted and Lewis acidity, thermal stability, and surface tunability. This review overviews recent advances in catalyst design, including metal doping, structural tuning, and hybridization with porous materials. These have significantly improved HMF yields -up to 80%- while enhancing catalyst selectivity and reusability. A systematic review with a descriptive-analytical approach was applied, analyzing literature from 2015 to 2025 across major scientific databases. Furthermore, challenges, including side-product formation and active site leaching, are highlighted alongside future perspectives for scalable and green HMF synthesis using Nb-based catalysts. This review aims to guide the rational development of modified Nb2O5 catalysts for efficient biomass transformation. These developments are crucial for advancing Nb-based catalytic platforms and unlocking the full potential of HMF in a circular, bio-based chemical industry.